PERAN KEPALA DESA DALAM PEMBUATAN AKTA DI BAWAH TANGAN YANG DILAKUKAN PARA PIHAK PEMEGANG HAK ATAS TANAH (Studi di Desa Selogudig Wetan Kecamatan Pajarakan Kabupaten Probolinggo) - Munib, Ali (JUSTNESS - Jurnal Hukun dan Agama, 2022)
Abstrack The freedom to make an agreement is the freedom of every individual. Put forward an open system by the parties referring to the provisions of Article 1320 of the Civil Code as a condition for the validity of an agreement. This study aims to identify and examine as well as analyze the public's perception of the making of private deeds and the role of the village government in tackling the rampant making of private deeds in the community. This research is an empirical legal research. The results of this study indicate that there are several reasons why the people of Selogudig Wetan Village still carry out buying and selling transactions that are only limited to making under-handed deeds, namely the low legal awareness regarding certainty of underhanded deeds, not knowing the mechanics of making authentic deeds involving PPAT and the absence of legal counseling that been carried out by the village government. Efforts that have been made by the village government in tackling the rampant making of underhand deeds are to hold legal counseling on the importance of making authentic deeds and to socialize to the public that the deed under the hands of the power of proof is only formal. Keywords: Underhand Deed, Community Perception, Government Effort